EVALUASI TINGKAT KEPUASAN PELAYANAN REVISI ANGGARAN - Achmad Zunaidi; Nurdianti Komariyah; Aziz Wahyu Suprayitno (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2022)
Stakeholder satisfaction is an important issue in public services organized by the bureaucracy. This study aims to measure the satisfaction of budget revision services organized by the Directorate of Budget for Human Development and Culture, Directorate General of Budget. The analytical tools used consist of the Customer Satisfaction Index (CSI), Service Quality (Servqual), and Importance Performance Analysis (IPA). CSI analysis is intended to determine the level of customer satisfaction. Meanwhile, Servqual analysis to identify the importance of each service dimension. IPA identify the level of importance of each service attribute as well as priority improvements that must be made. Respondents consisted of 110 employees of the Planning Bureau of ministries/agencies. Based on CSI analysis, the level of satisfaction with budget revision services is 87.70% and is in the